HUBUNGAN PRENATAL YOGA DENGAN TINGKAT KECEMASAN DAN KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III - Gunawan, Andra Destyan; Novia Fransiska Ngo; Nur Khoma Fatmawati (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
Quite a few women experienced anxiety and fear during pregnancy and nearing the labor process, while one of the effects of this situation can reduce sleep quality. One of the efforts that can be done to overcome these inconveniences is prenatal yoga. Based on preliminary studies, it was found that pregnant women who have been doing yoga experience a reduction of the complaints that they feel. This study aims to determine the relationship between prenatal yoga with anxiety level and sleep quality in third-trimester pregnant women. This research is observational research using pretest-posttest with control group design. The sampling method used was purposive sampling in accordance with the specified inclusion and exclusion criteria. This research samples were 32 respondents who were divided into 2 groups, which are the intervention group and control group. Data collection was carried out using a questionnaire to determine the level of anxiety and sleep quality of the respondents. Based on the bivariate results, there were differences of anxiety levels before and after prenatal yoga (p-value = 0.001), there were differences in sleep quality before and after prenatal yoga (p-value = 0,000), there was a relationship between prenatal yoga and anxiety levels (p-value = 0,001), and there was a relationship between prenatal yoga and sleep quality (p-value = 0,000). There were differences of anxiety level and quality of sleep before and after prenatal yoga. There was a relationship between prenatal yoga with anxiety levels and sleep quality.